Effect of Foliar Spraying with Pink Pigmented Facultative Methylotrophic Bacteria on the Growth and Productivity of Strawberry - shadia Ismail; Fafy Mohammed (Arab Universities Journal of Agricultural Sciences, 2023)
Pink-pigmented facultative methylotrophic bacteria (PPFM) isolated from cotton leaves was identified based on phenotypic and genotypic characteristics as Methylobacterium rodiotolerance. Two field experiments were conducted to investigate the effects of PPFM, methanol (10 and 30%) and a combination of bacteria and methanol on the growth, fruit quality, and yield of two strawberry cultivars (Florida and Festival). The main differences between the two cultivars are greater foliage fresh weight and early yield in cv. Florida while Festival cv. had a higher total yield per plant and greater anthocyanins and ascorbic acid contents. The greatest vegetative growth, dry matter percentage, potassium content, and carbohydrate content besides the earliest yield per plant were observed following spraying with PPFM or PPFM mixed with 10% methanol. Spraying with PPFM resulted in the highest total yield per plant, highest yield per feddan, and fruit quality. Spraying cv. Florida with PPFM resulted in the best early yield while spraying cv. Festival with PPFM resulted in the highest total yield and fruit quality. Spraying with PPFM appears to be the most efficient treatment for enhancing the total yield of Festival cv. by an average of 23.02 and 24.06 tons per feddan in the first and second seasons, respectively.